1975
DOI: 10.1073/pnas.72.5.1787
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptors for thyroid hormone: evidence for nonrandom distribution within chromatin.

Abstract: Chromatin receptor proteins appear to mediate some actions of thyroid hormone. In this study, sheared mammalian chromatin containing [125Itriiodo-thyronine (T3) bound by these receptors was separated using sucrose gradient velocity sedimentation. T3-receptor complexes were distributed throughout the chromatin fractions, but were enriched in the slowly sedimenting fractions. The latter contain most of the template capacity for RNA synthesis and most of the endogenous RNA polymerase activity but a minor portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Because thyroid hormone receptors and glucocorticoidreceptor complexes are found in the chromatin (3,35,36), it is possible that the changes in mRNA levels are due to hormonal regulation of transcription, as appears to be the case with sex steroids (37,38). However, it is not known, particularly for thyroid hormones, whether control of mRNA is generally responsible for other actions of the hormones.…”
Section: Discussionmentioning
confidence: 96%
“…Because thyroid hormone receptors and glucocorticoidreceptor complexes are found in the chromatin (3,35,36), it is possible that the changes in mRNA levels are due to hormonal regulation of transcription, as appears to be the case with sex steroids (37,38). However, it is not known, particularly for thyroid hormones, whether control of mRNA is generally responsible for other actions of the hormones.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of thyroid hormone was required for binding of its receptor to the growth hormone gene promoter, suggesting that thyroid hormone renders the receptor capable of recognizing specific gene regions. L-3,5,3'-Triiodothyronine (T3), the active form of thyroid hormone, modulates the expression of a number of genes (1,2), and this is ascribed to the association of T3 with receptors localized in chromatin (3). In rat pituitary tumor cells the concentration of growth hormone (GH) mRNA increases in response to physiological concentrations ofT3 (refs.…”
mentioning
confidence: 99%
“…H ) It was reported that specific receptor of thyroid hormones was also present nonhistone protein in chromatin. 15 ) These hormones were assumed to function by interaction with non-histone protein which regulated the gene expression.…”
Section: Resultsmentioning
confidence: 99%